Evaluation of the Shear Bond Strength of Orthodontic Adhesive Incorporated with Titanium Dioxide Nanoparticle: An In-vitro Study - M Ashfaq Ahmed; S Sumalatha; N Narendran; G Dinesh Nandakumar; A Agasthiya (Journal of Clinical and Diagnostic Research)
Introduction: White Spot Lesions (WSL) are a common problem in orthodontic treatment due to improper oral hygiene maintenance and plaque accumulation, which reduce the bond strength of the appliance. To address this issue, various bonding materials have been introduced over time to enhance the bond strength of adhesives. Recently, different kinds of nanoparticles have been added to composite resins with the goal of enhancing bonding efficiency without affecting bond strength. Aim: To evaluate the shear bond strength of Titanium Dioxide (TiO2) nanoparticle-incorporated orthodontic adhesive. Materials and Methods: The present in-vitro study was conducted in the Department of Orthodontics and Dentofacial Orthopaedics, Best Dental Science College, Madurai, Tamil Nadu, India, between July 2022 and December 2023. Study included 60 samples of extracted human maxillary first premolar teeth. The samples were equally divided into two groups. In group 1, brackets were bonded with conventional composite, and in group 2, brackets were bonded with TiO2 nanocomposite. The shear bond strength for each group was determined using a universal testing machine, and Adhesive Remnant Index (ARI) scores were also assessed. Statistical analysis was conducted using the Student t-test and Chi-square test to evaluate the differences between the groups. Results: The results of the study showed that the bond strength was significantly higher for the TiO2 nanocomposite group with mean±Standard Deviation (SD) of 14.3±1.21 MPa than for the conventional composite group with mean±SD of 12.9±1.05 MPa. This indicates that the TiO2 nanocomposite had significantly better bond strength than the conventional composite by 1.4 MPa (p-value=0.045). However, the ARI scores between the two groups were statistically not significant (p-value=0.682). Conclusion: In conclusion, incorporating TiO2 into the conventional composite significantly enhanced the bond strength of the composite.